Cortometraje, más que un instante : colección de cortometrajes mexicanos - Eimbcke, Fernando (realización); Eimbcke, Fernando (guión); Zabé, Alexis (fotógrafo); Torre, Santiago (montaje); Ruiz, Alexis (música); Gollás, Alejandra (actuación); Wilhelme, Alma (actuación); González, Evelyn (actuación) (Instituto Mexicano de Cinematografía)
Obra en 10 volúmenes (en la Biblioteca falta el 1)